Odyssey of the Mind: Using a Creative Problem-Solving Competition to Promote Career Readiness in Elementary School. Issue 3 (October 2017) - Wasik, Suzan Z.; Barrow, Jennifer
The career landscape has changed dramatically over the past two decades with the adoption of technology and an increasingly global and virtual workforce. As a result, schools and academic institutions must go beyond current curriculum to teach and develop the new skills and competencies that are required to keep pace with the demands of careers in the 21st century. This article examines the adoption of the Odyssey of the Mind program—a competitive creative problem-solving model—as a way to teach, develop, and demonstrate social emotional intelligence and other related soft skills that are necessary to master for current and future career success.